1995
DOI: 10.1177/002193479502500307
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Perceptions on Interpersonal Interactions in an African American/Asian American Housing Project

Abstract: An increasing number of communities in the United States are ethnically diverse. In recent decades, large numbers of immigrants, for example, Mexicans, Central Americans, Latin Americans, and Asian Americans, have been incorporated into predominantly African American urban neighborhoods and communities. An understanding of the nature of interactions in these ethnically, culturally, and sometimes linguistically diverse environments is necessary to enable community members and leaders to deal with changing inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…In this case, the context in which participation occurred was clearly related to Hmong participation in multiethnic communities. Since interaction and participation in multiethnic communities are low and most often occur within ethnic groups, not between groups~Guthrie & Hutchinson, 1995;Jong, 1989;Humphreys & Woods, 1993!, attention to the climate in ethnically mixed communities and how it influences participation is essential. Most researchers agree that participation is facilitated or inhibited by both individual and contextual characteristics and the complex ways in which they interact~e.g., Wandersman, 1984;Wandersman & Giamartino, 1980!. The findings from this study suggest that the extent to which Hmong felt included and accepted in their communities was related to their participation.…”
Section: • Participation and Empowermentmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the context in which participation occurred was clearly related to Hmong participation in multiethnic communities. Since interaction and participation in multiethnic communities are low and most often occur within ethnic groups, not between groups~Guthrie & Hutchinson, 1995;Jong, 1989;Humphreys & Woods, 1993!, attention to the climate in ethnically mixed communities and how it influences participation is essential. Most researchers agree that participation is facilitated or inhibited by both individual and contextual characteristics and the complex ways in which they interact~e.g., Wandersman, 1984;Wandersman & Giamartino, 1980!. The findings from this study suggest that the extent to which Hmong felt included and accepted in their communities was related to their participation.…”
Section: • Participation and Empowermentmentioning
confidence: 99%
“…Most researchers agree that participation is facilitated or inhibited by both individual and contextual characteristics and the complex ways in which they interact~e.g., Wandersman, 1984;Wandersman & Giamartino, 1980!. The findings from this study suggest that the extent to which Hmong felt included and accepted in their communities was related to their participation. First, similar to previous researchers~e.g., Guthrie & Hutchinson, 1995;Hein, 1995!, our data suggested that Hmong residents were less likely to participate due to negative intergroup relations. Attention to intergroup dynamics is critical for refugees who are often a minority in their resettlement communities.…”
Section: • Participation and Empowermentmentioning
confidence: 99%
See 1 more Smart Citation
“…The Model Minority Stereotype was predominantly a political weapon used during the 1960s (Success Story of One Minority Group, 1966) to convey that Asian Americans overcame discrimination with determination and hard work and that African Americans' complaints of inequality were a result of their own laziness. This placed the blame of racial inequality on the minority groups themselves (Osajima, 1988), fueling resentment between Asian Americans and other racial minority groups (Guthrie & Hutchinson, 1995;Kim, 2(X)4) and causing White Americans to view Asian Americans as a threat (Toupin & Son, 1991). The Model Minority Stereotype is also associated with the misconceptions that Asian American students do not need academic or personal help or that they are mentally healthier compared to other groups (Sue & Sue, 2008), Contrary to these popular myths, the Frances C. Shen, Psychology Department, University of Illinois Springfield; Yu-Wei Wang and Jane L. Swanson, Department of Psychology, Southem Illinois University Carbondale.…”
mentioning
confidence: 99%
“…However, earlier studies have shown that in spite of this strong sense of loyalty to family, a prevalent stereotype is that Asian Americans are viewed as being unsociable with members of the dominant group (Guthrie & Hutchinson, 1995;Hughes & Baldwin, 2002;Lin et al, 2005). Given these claims about perception of sociability with members of the in-group and the dominant group, the following hypothesis will be investigated.…”
mentioning
confidence: 99%